Invasion of the Charitable Kind - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2009)
Are sustained philanthropic contributions over a long-term period more attractive than a one-off donation? It may seem so at first. However, continuous funding calls for non-profit organisations to enter into a high-involvement relationship with donors. “It is as important for the donors to learn and understand the non-profit sector and social issues, as it is for them to give and volunteer,” explained Ruth Jones, executive director of SVP International.